Rheumatologic Manifestations in Hepatitis C Patients: A Multicentric Study - Bhutta, Musharaf Khalid; Rind, Amir Abbas; Butt, Suha Tayyab; Attique, Hamna; Nazir, Maheen; Mumtaz, Shumaila (Students’ Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: The World Health Organization (WHO) has estimated that about 180 million people are infected with the Hepatitis C virus (HCV). One in every 20 Pakistanis has been already infected with this infection. With confusing rheumatological signs and symptoms of arthritis and Hepatitis C, timely diagnosis and treatment have become a challenge for clinicians. Objectives: This study aims to determine the Rheumatological Manifestations in Patients diagnosed with Hepatitis C, and to investigate the relationship of rheumatological manifestations with the chronicity of hepatitis C. Material and methods: The cross-study was carried out at hepatology clinics of the three allied public sector hospitals situated in Rawalpindi for 2 years due to the pandemic. 114 patients of either gender were recruited. Patients were evaluated for different rheumatological features throughout history and examination. Patients with Hepatitis C, HCV positive were included and patients with HBV and Paraneoplastic syndrome, previously known as musculoskeletal disease, CKD, DM, were excluded. Results: Out of 114 patients, 52 were male and 62 females. Duration of diagnosis of 37 patients less than 6 months and of 77 patients more than 6 months. The study showed a significant relation between duration since diagnosis(chronicity) and positive ultrasound findings, including fatty liver and cirrhosis, arthralgias, sicca symptoms, numbness and paresthesia and a significant relation between inflammatory arthritis and ALT levels. SICCA symptoms manifestation also showed a significant relation with a high SSS fibromyalgia score and high bilirubin levels. Conclusions: With chronicity of Hepatitis C, patients manifested more Rheumatological signs and symptoms confusing the diagnosis with rheumatoid arthritis.